Impact of Financial Fundamentals on Firm Value: Evidence from Cosmetics and Household Goods Sector - Ahlannisa, Lala; Simon, Zainal Zawir; Oktavia, Dinda (Research of Economics and Business, 2024)
This study proposes to understand the influence of return on assets, current ratio, debt-to-equity ratio, and total asset turnover on firm value. The research method used is quantitative and uses secondary data, namely the corporate sub-sector cosmetics and household goods listed on the Indonesian Stock Exchange (IDX). The sample used is as many as 6 firms, period 2015-2020 through the purposive sampling method. The method of analysis of panel data. The results obtained in this study show that the simultaneous return on assets, current ratio, debt-to-equity ratio, and total asset turnover affect the firm value. A partial return on assets effect has a negative and significant impact on firm value, a current ratio effect has a positive and significant impact on firm value, a debt to equity ratio has no significant effect on firm value, and total asset turnover has a positive and significant effect on firm value. The managerial implication of these findings is the importance of management in optimizing the use of assets, maintaining healthy financial ratios, and managing the firm's capital structure wisely. Managers need to pay attention to these financial performance indicators of firm value.